Presence : philosophy, history, and cultural theory for the twenty-first century - Ghosh, Ranjan; Kleinberg, Ethan, 1967-; Kleinberg, Ethan, 1967- (Cornell University Press, 2013)
The philosophy of "presence" seeks to challenge current understandings of meaning and understanding. One can trace its origins back to Vico, Dilthey, and Heidegger, though its more immediate exponents include Jean-Luc Nancy, Hans Ulrich Gumbrecht, and such contemporary philosophers of history as Frank Ankersmit and Eelco Runia. The theoretical paradigm of presence conveys how the past is literally with us in the present in significant and material ways: Things we cannot touch nonetheless touch us. This makes presence a post-linguistic or post-discursive theory that challenges current understandings of "meaning" and "interpretation." Presence provides an overview of the concept and surveys both its weaknesses and its possible uses. In this book, Ethan Kleinberg and Ranjan Ghosh bring together an interdisciplinary group of contributors to explore the possibilities and limitations of presence from a variety of perspectives--history, sociology, literature, cultural theory, media studies, photography, memory, and political theory. The book features critical engagements with the presence paradigm within intellectual history, literary criticism, and the philosophy of history. In three original case studies, presence illuminates the relationships among photography, the past, memory, and the Other. What these diverse but overlapping essays have in common is a shared commitment to investigate the attempt to reconnect meaning with something "real" and to push the paradigm of presence beyond its current uses. The volume is thus an important intervention in the most fundamental debates within the humanities today. Contributors: Bill Ashcroft, University of New South Wales; Mark Bevir, University of California, Berkeley; Susan A. Crane, University of Arizona; Ranjan Ghosh, University of North Bengal; Suman Gupta, Open University Ethan Kleinberg, Wesleyan University; John Michael, University of Rochester; Vincent P. Pecora, University of Utah; Roger I. Simon